Analysis of MSME Development in the Digital Era Using the Business Model Canvas from an Islamic Economic Perspective - Tria Manda Sari; Reni Ria Armayani Hasibuan; Nurbaiti Nurbaiti (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have significant potential to leverage technology to expand their markets and become more competitive in the digital era. This study uses the Business Model Canvas (BMC) approach to examine MSME development strategies in the digital era within the Medan Orang Bazar Community. A descriptive qualitative research methodology was employed, and information was collected through observation, interviews, and documentation. The Miles and Huberman model was used to analyze the data. The results indicate that the MSME development plan within the Medan Orang Bazar Community centers on maximizing the nine components of the Business Model Canvas. Young individuals and young families active on social media constitute this customer segment, offering distinctive local goods at affordable prices and attractive packaging. The plan was developed in collaboration with local communities and influencers, and using digital platforms such as Shopee, Instagram, and TikTok. Active engagement on social media and loyalty programs maintain customer relationships. This approach demonstrates how MSMEs can utilize the Business Model Canvas as a roadmap to develop their companies creatively, effectively, and sustainably in the digital era. The findings also revealed that some MSMEs in this community inherently apply Islamic business principles, particularly in terms of offering halal products, honest promotional practices, and community-based economic empowerment (taʿawun), indicating that the BMC framework can be complemented with a sharia-based business development perspective.